Annual Report on Actions to Address Climate Change (2018) - Xie, Fuzhan; Liu, Yaming (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book focuses on China's efforts to address climate change on both the strategic and practical levels since the Katowice Climate Change Conference. Featured articles provide readers with both an overview and detailed discussions of topics such as assessment of low-carbon city development, building climate resilience, global climate governance, just transition, climate finance, and others. All the contributors are leading experts in the field from Research Institute for Eco-civilization (formerly Institute of Urban and Environmental Studies), Chinese Academy of Social Sciences, and China Meteorological Administration.
Chapter 1. Ten Years of Actions on Climate Change Have Paid off -- Chapter 2. Effectiveness Assessment on Low-carbon City Construction in China -- Chapter 3. Opportunities and Challenges for China to Lead Global Climate Governance Against the Backdrop of De-globalization -- Chapter 4. Reflections and Recommendations on China's Solutions to Climate Change in the Talanoa Dialogue -- Chapter 5. Towards a Climate Resilience Society: Challenges and Prospects -- Chapter 6. New Changes in Global Climate Governance and the Rise of Non-governmental Organizations -- Chapter 7. Development Trends, Possible Impacts, and Countermeasures of the Powering Past Coal Alliance -- Chapter 8. The Status Quo, Problems and Strategic Countermeasures of South-South Cooperation on Climate Change -- Chapter 9. The Evolution of the Rule-based system for Global Climate Governance Based on Science and Practices -- Chapter 10. The International Progress of Making Concerted Efforts to Promote Climate Action and Sustainable Development -- Chapter 11. Assessment on the Synergistic Effect of China's Urban Air Pollution Control Policies and Greenhouse Gas Emissions Reduction -- Chapter 12. The Status Quo and Prospect of the Development of China's Energy Conservation Service Industry -- Chapter 13. Tackling Climate Change and Just Transition -- Chapter 14. The Effects of Different Carbon Prices on the International Competitiveness of the Industries Covered by China's National Carbon -- Chapter 15. The Global Climate Finance System in Transition and China's Responses -- Chapter 16. Cryospheric Science Needs to Provide Higher-quality Services in the Context of the New Climate Normals -- Chapter 17. Impacts of Extreme Weather Events on Urban Living, Production, and Ecology and the Adaptation Strategies.
Keywords: Power resources; Environmental economics; Bioclimatology; Resource and Environmental Economics; Climate Change Ecology